Unraveling Iris ensata Thunb: a pharmacognostical, physicochemical and HPLC-assisted phytochemical investigation - Khan, Sania; Alam, Shamshad; Azhar, Mohd; Shamshad, Sameera; Fatima, Malik Nuzhat; Farha, Samreen; Hasan, Saleha (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Iris ensata Thunb, commonly known as the Japanese iris, is a species of flowering plant in the Iris family (Iridaceae). Native to Japan, China, Korea, and Russia, it thrives in wetland environments and is often found near ponds and streams. Methods: To standardize the test drug, various analytical techniques were employed, including organoleptic evaluation, extractive value determination, ash content analysis, phytochemical screening, elemental analysis, fluorescence study, and HPLC profiling. Results: The findings revealed that the total ash content was 6.98%, while the water-soluble and alcohol-soluble extractive values were 13.3% and 9.81%, respectively. The loss on drying was recorded at 4.21%, foreign matter was 0.66% and the bulk density was found to be 0.63%. The HPLC analysis displayed 18 peaks, with peak 02 and peak 03 being the most significant, showing area concentrations and retention times of 54.676% at 2.828 minutes and 43.822% at 3.051 minutes, respectively. Conclusions: This study provided essential reference data for ensuring the quality, purity, and identification of future batches of I. ensata Thunb contributing to its standardization in medicinal applications.